Efficacy of shatavaryadi ksheerapaka basti in enhancing the maternal nourishment in garbha kshaya along with relieving the pregnancy discomforts - Suprabha Kunjibettu; Laxmi Priya Dei; Nalini Anand (Wolters Kluwer Medknow Publications, 2021)
Background: Garbha Kshaya is considered among the abnormalities of fetus (Garbha Vyapads), associated with growth-related disorders, especially due to maternal undernourishment. Garbha Kshaya comprises of diminished fundal height (Anunnata Kukshi) and reduced fetal movement (Garbhaaspandana) possibly due to reduced liquor amni. Ayurveda mentions Ksheera Basti as classical treatment in its management, wherein nourishment is provided through milk-infused medicated enema. Materials and Methods: Pregnant patients fulfilling the inclusion criteria were randomly divided into two groups. Forty-one patients in Shatavaryadi Ksheerapaka Basti group (trial) were administered with Shatavaryadi Ksheerapaka Basti consisting of Bala, Shatavari and Arjuna for a period of 10 days daily once in the morning. Twenty patients in L-Arginine group (control) were administered with L-Arginine 6.5 g sachet BD (in divided dose) with 1 glass water for 10 days. Results: Improvement was observed in the fetal movements (P ≤ 0.001) and maternal wellbeing (P ≤ 0.001) in Ksheerapaka Basti group. Abdominal girth (P ≤ 0.001) and symphysis fundal height (P ≤ 0.001), and maternal weight gain (P ≤ 0.001) showed highly significant results in Ksheerapaka Basti group. Pregnancy related discomforts such as Adhmana (P ≤ 0.001), Anidra (P = 0.002), Aruchi (P ≤ 0.001), Bhrama (P = 0.009), Daurbalya (P ≤ 0.001), Gaurava (P ≤ 0.001), Katishoola (P ≤ 0.001), Malabaddhata (P ≤ 0.001), Padashoola (P ≤ 0.001), Padashopha (P ≤ 0.001), Shrama (P ≤ 0.001), and Uras Daha (P ≤ 0.001) showed significant improvement in Ksheerapaka Basti group. Conclusion: Shatavaryadi Ksheerapaka Basti showed encouraging results in improving the fetal movements, maternal weight, and growth measurements such as abdominal girth, symphisis fundal height. It also showed promising results in overcoming the physiological discomforts of pregnancy and maintaining the overall maternal health.